The Manuscripts of the Middle English Lay Folks’ Mass Book in Context - Smith, Jeremy J. (Studia Anglica Posnaniensia, 2021)
This paper, part of a long-term programme of research into the forms and functions of the vernacular in late medieval liturgical practice in England, offers a “cultural map” of the Middle English poem known as The Lay Folks’ Mass Book (LFMB). Comparatively little research has been undertaken on LFMB since Simmons’s edition of 1879. However, new developments in the study of manuscript-reception in particular regions of the Middle English-speaking areas of Britain, combined with greater understanding of the cultural dynamics of “manuscript miscellanies” and of medieval liturgical practice, allow us to reconstruct with greater certainty the contexts within which LFMB was copied and used. LFMB survives in nine late medieval copies, but each copy presented a distinct version of the text. This article brings together linguistic, codicological, liturgical, and textual information, showing in detail how the poem was repurposed for a range of different cultural functions. In geographical terms, it seems clear that the work circulated in Derbyshire/Nottinghamshire, in Yorkshire, and in Norfolk, and can thus be related to other texts circulating in those areas. Some versions are likely to have emerged in parochial settings, possibly owned by local priests. There is also evidence that the text could be deployed in monastic contexts, while other versions probably formed part of the reading of pious gentry. What emerges from a study of the codices in which copies of LFMB were transmitted is that a range of shaping sensibilities for these manuscripts may be distinguished; the authorial role in texts such as LFMB was balanced with that of their copyists and audiences. In the manuscripts containing LFMB creativity was negotiated within textually-transmitted communities of practice.